“DANCING” MERCHANTS BEYOND THE EMPIRES ON THE SILK ROAD - N. T. Nurulla-Khodjaeva (MGIMO University Press, 2017)
The article is devoted to political and cultural heritage of Sogdians (“merchants outside empires”). This is the Central Asian people, who lived in a period from around the 6th century BC. until the middle of the Middle Ages, and then were dispersed in the vastness of Khorasan region. Throughout its history the Sogdians played the role of the most important trade intermediaries on some segments of the Silk Road, many researchers today consider “Silk Road” and “Sogdian Trade Network” as synonyms notions. Sogdians were unique in their inclination not only to develop new products, but also to proliferate their own reinterpretation of new, mostly imported ideas. This is especially evident in their relations with the Chinese, including the period of the Tang dynasty (618-907), i.e., “Golden age” in the history of China. The article for the first time in Russian research literature represents Sogdians as a people who managed to influence the Eurasian cultural dynamics by introducing the principle of deterritorialization into relations with close and far neighbors. Most modern historians in Central Asia tend to ignore the contribution to “their” history from “strangers”, neither mediators, nor neighbors. The appeal to the intellectual heritage of Sogdians as a people who promoted the transformation of the region into a crossroads of cultures would open the possibility of developing intellectual pluralism in each of the Central Asian countries today and would allow accelerating the creative modernization of the region as a whole.